2020
DOI: 10.1016/j.ptsp.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical characteristics and severity of gradual onset injuries in recreational road cyclists: A cross-sectional study in 21,824 cyclists - SAFER XIII

Abstract: Objectives: Prevalence, clinical characteristics and severity of gradual onset injuries (GOIs) in cyclists are poorly documented. We determine the prevalence, anatomical regions/sites affected and severity of GOIs among entrants in a community-based mass participation event. Design: Cross-sectional study; Setting: Cape Town Cycle Tour; Participants: Race entrants. Main outcome measures: Of 35,914 entrants, 27,349 completed pre-race medical questionnaires. We studied 21,824 consenting cyclists (60.8% of entrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…As regiões anatômicas mais acometidas por lesões foram os joelhos (4,55 e 4,52%), tornozelos/pés (4,55 e 2,01%), das mulheres e homens, respectivamente, e na parte inferior das costas dos homens (4,52%). Estes achados assemelham-se com dados já relatados que verificaram que as regiões anatômicas mais acometidas por lesões foram os joelhos (26,3%), ombros (13%) e parte inferior das costas (11,5%) 9 . Adicionalmente, os dados do National Interscholastic Cycling Association Injury Surveillance System revelam que as regiões mais acometidas por lesões em atletas de MTB são: cabeça (22,2%), punhos/mãos (19,0%) e ombro (15,7%) 10 .…”
Section: Discussionunclassified
“…As regiões anatômicas mais acometidas por lesões foram os joelhos (4,55 e 4,52%), tornozelos/pés (4,55 e 2,01%), das mulheres e homens, respectivamente, e na parte inferior das costas dos homens (4,52%). Estes achados assemelham-se com dados já relatados que verificaram que as regiões anatômicas mais acometidas por lesões foram os joelhos (26,3%), ombros (13%) e parte inferior das costas (11,5%) 9 . Adicionalmente, os dados do National Interscholastic Cycling Association Injury Surveillance System revelam que as regiões mais acometidas por lesões em atletas de MTB são: cabeça (22,2%), punhos/mãos (19,0%) e ombro (15,7%) 10 .…”
Section: Discussionunclassified
“…10,31,32,34,36À38 Methodological quality items for each included study are reported in Table 2. Of seventeen studies, nine did not use sample frame appropriate to address the target population, 12,31,32,34À36,38,40,41 seventeen did not sample study participants in an appropriate way, 10,12,27À41 fourteen did not have appropriate sample size, 10,12,27À29,31À33,35,37À41 five did not describe subjects and the setting in detail, 32,[34][35][36][37] one did not analyze data with sufficient coverage of the identified sample, 31 four did not use valid methods for the identification of overuse injuries, 10,31,34,38 no study present measures in a standard and reliable way for all participants, three did not have appropriate statistical analysis, 34,36,37 and three did not reach appropriate response rate. 10,29,31 Prevalence of overuse injuries in individual and team sports Pooling of 24 704 participants, 22 748 from individual sports and 1956 from team sports, from the 17 included studies was done to estimate the prevalence of overuse injury in individual and team sports separately (Fig.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…39À41 Regarding the study design, thirteen were prospective cohort studies, 12,27À30,32,35À41 two studies were descriptive epidemiological studies, 31,33 and two were cross-sectional studies. 10,34 For overuse injuries measurement, nine studies used the Oslo Sports Trauma Research Center questionnaire (OSTRC), 12,27,28,30,32,33,36,39,40 four used the Oslo Sports Trauma Research Center questionnaire on health problems (OSTRC-H), 29,35,37,41 one used an injury record form, 31 two used a questionnaire on injuries originally developed by the authors, 10,34 one used medical record data. 38 Thirteen studies reported period prevalence, 10,12,27,28,30,32,33,35À39,41 among them, three studies reported pre-competition prevalence, 27,40,41 two studies reported pre-and during the season prevalence, 35,36 four studies reported prevalence during the season, 12,32,33,37 and five studies did not specify when the prevalence measure was taken.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that cycling is considered a safe and low-impact activity, a number of acute, chronic and overuse injuries have been linked to its practice (Dinu et al, 2019;Rasmussen et al, 2016). In regard to overuse injuries, low back pain (LBP) has been reported as one of the areas with a high prevalence of injuries in recent studies among recreational cyclists (11.5%) (Francois Du Toit et al, 2020), mountain bikers (23%) (Lebec et al, 2014), and road cyclists (45%) (Priego Quesada et al, 2019).…”
Section: Introductionmentioning
confidence: 99%